On the Question of Compulsory Dissolution of Business Entities - Петров, Євген Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is devoted to the study of the legal nature of the forced termination of business entities as one of the varieties of legal entities. Based on an analysis of doctrinal approaches, legislation and judicial practice the author comes to the conclusion that the coincidence of features inherent in the forced cessation of companies and administrative and economic sanctions that can be considered involuntary liquidation of such legal entities as a form of administrative and economic sanctions.